Identification of Biological Risk Genes and Candidate Drugs for Psoriasis Vulgaris by Utilizing the Genomic Information - Lisza Niarisessa; Anisa Nova Puspitaningrum; Arief Rahman Afief; Dyah Aryani Perwitasari; Wirawan Adikusuma; Rocky Cheung; Abdi Wira Septama; Lalu Muhammad Irham (Borneo Journal of Pharmacy, 2023)
Psoriasis is an autoimmune disease that causes inflammation on the skin's surface, characterized by the appearance of pink plaques covered with white scales. Currently, the availability of psoriasis vulgaris therapy is still limited. Therefore, considering the discovery of new drug candidates by utilizing genetic variations, such as single nucleotide polymorphisms (SNP) through drug repurposing, is a profitable method. The SNP associated with psoriasis was obtained from Genome-Wide Association Studies (GWAS) and Phenom-Wide Association Studies (PheWAS) databases. We identified 245 SNPs associated with psoriasis vulgaris with criteria of r2 >0.8. To prioritize the candidate of a gene associated with psoriasis, we used five criteria of functional annotation (missense/nonsense, cis-eQTL, PPI, KEGG, and KO mice) where if there were more than two criteria of assessment, they were defined as the risk gene of psoriasis vulgaris. Fifty-two genes were identified as the risk gene of psoriasis vulgaris, then expanded using the STRING database to obtain more gene candidates of drug targets. The result is 104 genes candidates for drug targets, of which 24 overlapped with 96 drugs, according to DrugBank. Of the 96 drugs that have been approved for other indications, we found that five drugs (ustekinumab, tildrakizumab, risankizumab, guselkumab, and etanercept) are currently in clinical trials for the treatment of psoriasis that target two genes (IL23A and TNF). We argue that these two genes are the most promising targets based on their high target scores on functional annotations. This research explains the potential that utilizing genomic variation can contribute to drug discovery.